2018
DOI: 10.12705/674.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variation obscures species diversity in southern European populations of the moss genus Ceratodon

Abstract: A major problem in taxonomy is to determine if morphological variation in field-collected specimens is caused by genetic differentiation, and therefore corresponds to evolutionary distinct units, or is caused by environmental variation acting on a single interbreeding population. To evaluate the effect of environmental variation on the taxonomy of the moss genus Ceratodon, we compared biometric analyses based on 22 morphological characters on both field-collected plants and cultivated plants to a clustering ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Despite the long period of isolation suggested by the sequence divergence between C. purpureus and the new species, we have found evidence of interspecific hybridization, suggesting that the new species apparently has retained the capacity for sexual reproduction. In a separate paper, we discuss the taxonomic implications of this discovery (Nieto‐Lugilde et al., ). Here, we use genealogical and genome size data to make inferences regarding the genetic architecture of speciation, and the demographic parameters that permit such divergence.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Despite the long period of isolation suggested by the sequence divergence between C. purpureus and the new species, we have found evidence of interspecific hybridization, suggesting that the new species apparently has retained the capacity for sexual reproduction. In a separate paper, we discuss the taxonomic implications of this discovery (Nieto‐Lugilde et al., ). Here, we use genealogical and genome size data to make inferences regarding the genetic architecture of speciation, and the demographic parameters that permit such divergence.…”
Section: Discussionmentioning
confidence: 89%
“…The two best‐studied sympatric speciation mechanisms in plants are polyploidy and the evolution of self‐fertilization (Barringer, ). Here, we have shown that the evolution of a new species, closely related to the cosmopolitan Ceratodon purpureus , was associated with a 25% increase in genome size and a significant decrease in frequency of males (Nieto‐Lugilde et al., ). Surprisingly, although we have found neither males nor evidence of recent sexual reproduction (i.e., sporophytes) in the new species, the genetic diversity among members of this species is relatively high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the initiation of in vitro cultures from spores appears to be more successful than that from gametophores, due to the inner sterile conditions within the sporophyte capsules. However, cultures can be derived from gametophytes, but to significantly lesser extent (Sokal et al 1997;Sabovljević et al 2003;Nieto-Lugilde et al 2018), and it is easier to start the axenic bryophyte cultures from spores originating from unopened capsules if no dormant spores or endophytes are present (e.g. Sabovljević et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid bryophytes with different ploidy level earlier cytological techniques are gradually replaced by improved methods to compare chromosome morphology, ploidy level and estimate DNa content e.g. the squash technique (boisselier-Dubayle & bischler 1998;boisselier-Dubayle et al 1998a;boisselier-Dubayle et al 1998b;orzechowska et al 2010), the fluorochrome 4, 6-diamidino-2phenylindole (DaPI) technique (abderrahman 1998; abderrahman 2004; buczkowska et al 2004), flow cytometry (Såstad et al 2001;ricca et al 2008;Karlin et al 2009;Košnar & Kolář 2009;Orzechowska et al 2010;ricca et al 2011;buczkowska et al 2012;Nieto-lugilde et al 2018), Fluorescent differential staining, C-banding and fluorescent in situ hybridization (FISh) with 26S and 5S ribosomal DNa probes (orzechowska et al 2010), Feulgen DNa image densitometry (ricca et al 2008;Karlin et al 2009;Kyrkjeeide et al 2019) and ploidy estimation by microsatellite pattern (Karlin et al 2013(Karlin et al , 2014. The use of fluorescent in situ hybridization (FISh) of specific DNa probes to specific chromosomes or chromosome segments has recently proved straightforward and useful in studies of…”
Section: Second Period (1988-present): Hybrid Characterization Based On Combined Methods Of Cellular Ploidy Determination Biochemical Promentioning
confidence: 99%